Strand 3: Geekgirls or Cybersisters? Constructing Feminist Spaces for Learning in Cyberspace - Webb, Sue (Proceedings of the International Conference on Networked Learning, 1998)
This paper draws on action research exploring the introduction of networked learning into a Women's Studies degree programme. The paper describes how examples of materials were developed for the course web-site and considers whether or not the Internet can be a feminist space for learning. Accounts of the feminist frameworks which have informed the Women's Studies learning and teaching are provided, along with two competing stories about women's access and experiences of computer mediated communications for learning, and continuing personal and professional development. The location and perceptions of the students within these debates are discussed, as well as the extent to which the web-based framework has encouraged students co explore the Internet for themselves, and begin to weave and spin their own stories. What this has meant for the learners is explored. Have they become geekgirls or do they see the Internet as a way of linking with other cybersisters? The paper concludes chat on-line learning may help to empower this particular group, as long as it encourages chem to become self directed learners. There is evidence that not only does it provide access to resources, it also becomes a repository for feminist materials that might otherwise be lost or difficult to trace, and it offers a means of communicating and extending feminist activity and debate both locally and globally, in the context of learning new skills and identities.